An Experimental Investigation Into the Colonization of Concealed Cadavers by Necrophagous Blowflies. Issue 1 (24th October 2015) - Charabidze, D.; Hedouin, V.; Gosset, D.
Abstract : We used seven baited boxes with different combinations of access holes and odor diffusion surfaces to study the arrival of necrophagous flies. During laboratory experiments, 30 gravid Lucilia sericata females were kept in a chamber with one of the boxes. The box with the largest odor diffusion surface (99 cm 2 ) combined with the lowest accessibility (one 1 cm 2 entrance hole) was entered least (5 ± 3.7 flies per run). In contrast, the most frequently entered box (one 9 cm 2 entrance hole with no additional odor diffusion surface) caught a mean of 24.6 ± 3.4 flies per run. These results indicate that 1) L. sericata entered nearly inaccessible places and 2) both odor diffusion and accessibility impacted the number of flies caught. During field experiments, the seven boxes were placed together outdoors. The box with the most entrances (ten 9-cm 2 holes) caught the most flies (55.6–99.4% of the total). Only a few flies entered the other boxes. Access to the less accessible boxes (poor odor diffusion and small entrances) was also delayed. The major conclusions of the field experiments are that 1) boxes with low accessibility took longer to be accessed; 2) larger odor diffusion surfaces were more attractive to flies; and 3) flies accessed boxes more readily through larger holes than through an equivalent surface area made up of smaller holes. With these conclusions in mind, attempts to quantify the preappearance interval or to interpret the number of flies observed in indoor forensic entomology cases should be approached with caution.